Potensi produksi dan ekonomi biogas serta implikasinya pada kesehatan manusia, ternak dan lingkungan (Faculty of Animal Science, Universitas Brawijaya, 2013)
ABSTRACT: The purpose of this research was to find out biogas production on national scale, Malang District, and one of the villages in Ngantang, Malang District. Besides, the aim of this research is to find out the influence of biogas digester on human health, animal, and environment. This research was done using literature study and secondary data taken from Sumber Makmur Cooperation in Ngantang and Animal Health and Livestock Bureau in Malang District. The result of this research shows the potency of biogas production in Indonesia is huge. The amount of cows and cattles in Indonesia is around 15 million heads could produce biogas 9 million m3/day or 3285 million m3/month. If 1 m3 biogass equal to 0,62 lt gasoline, so 3285 million m3/month biogass equal to 2,036 billion of gasoline. If biogass used by Indonesian people as alternative energy, so it can save Rp 22,4 billion/year (price of gasoline Rp 11.000). The amount of cows and cattles in Malang District were 315.326 heads and potency of biogass production about 189.196 m3/day or 68.110.416 m3/year. While the total cattles and cows in Waturejo village, Ngantang, Malang District were 1532 tails, the potency of the gas production about 919.2 m3/day or 335.508 m3/year. Processing manure into biogas is beneficial for human, livestock and environment’s health because it reduces release of gases such as methane and CO2 into the atmosphere, reduces pathogens contamination to foodstuffs such as vegetables and milk and prevents environmental pollutions by pathogens that can cause death to humans and livestock. Key words: biogas,economic and production potency, health